Pelaksanaan Kegiatan Ekstrakurikuler Keagamaan dalam Membentuk Nilai-Nilai Pendidikan Agama Islam di Madrasah Tsanawiyah Darul Ulum Waru Sidoarjo - Muhammad Nabil Akmal; Eli Masnawati (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research is motivated by the problem of moral and moral degradation of students which is currently widespread. Therefore, religious extracurricular activities at MTs Darul Ulum Waru are present as a curative solution for the current generation and preventive for future generations. This article is the result of field research using qualitative research methods. Data collection was carried out through observation, interviews and documentation. Then the data results were analyzed using descriptive research. The results of the research show that the formation of Islamic religious education values ​​in students at Madrasah Tsanawiyah Darul Ulum Waru Sidoarjo has begun to appear, is developing well and has begun to be implemented in everyday life. The factors that influence continuity during the activity process are oneself, teachers, family and the environment. The internal supporting factors include the many parties who support the continuity of activities, the availability of supporting facilities and infrastructure, the high level of enthusiasm of students. Meanwhile, externally, namely competent trainers, extensive organizational relationships and various events/competitions at various levels. Internally, the problems found were the low interest of students in taking part in extra qiro'ah and the busyness of trainers, while from an external perspective, namely parental permission.